Platelets promote osteosarcoma cell growth through activation of the platelet‐derived growth factor receptor‐Akt signaling axis. Issue 8 (28th July 2014) - Takagi, Satoshi; Takemoto, Ai; Takami, Miho; Oh‐hara, Tomoko; Fujita, Naoya
<x xml:space="preserve">Abstract</x> Analysis of phospho‐antibody arrays revealed that co‐culture of osteosarcoma cells with platelets induced the phosphorylation of PDGFR and Akt. Detailed analysis suggest that PDGF released from platelets plays an important role in the proliferation of osteosarcomas by activating the PDGFR and then Akt. Our results suggest that inhibitors that specifically target osteosarcoma‐platelet interactions may eradicate osteosarcomas. <boxed-text content-type="graphic" id="cas12464-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>